Simulation of electron density maps for two-dimensional crystal structures using Mathematica - Delatorre, P.; de Azevedo, W. F. (Munksgaard Int Publ Ltd, 2001)
The simulations presented here are based on the program Mathematica as a tool to present electron density maps of two-dimensional crystal structures. The models give further insights into the relationship between the thermal displacement parameters and the quality of the electron density maps. Furthermore, users can readily test the effects of several crystallographic parameters on the electron density maps, such as, the number of reflections, the thermal displacement parameters and the unit-cell dimensions.